Adult‐onset very‐long‐chain acyl‐CoA dehydrogenase deficiency (VLCADD). (24th July 2020) - Fatehi, F.; Okhovat, A. A.; Nilipour, Y.; Mroczek, M.; Straub, V.; Töpf, A.; Palibrk, A.; Peric, S.; Rakocevic Stojanovic, V.; Najmabadi, H.; Nafissi, S.
Abstract : Background and purpose: Very‐long‐chain acyl‐CoA dehydrogenase deficiency (VLCADD) is a hereditary disorder of mitochondrial long‐chain fatty acid oxidation that has variable presentations, including exercise intolerance, cardiomyopathy and liver disease. The aim of this study was to describe the clinical and genetic manifestations of six patients with adult‐onset VLCADD. Methods: In this study, the clinical, pathological and genetic findings of six adult patients (four from Iran and two from Serbia) with VLCADD and their response to treatment are described. Results: The median (range) age of patients at first visit was 31 (27–38) years, and the median (range) age of onset was 26.5 (19–33) years. Parental consanguinity was present for four patients. Four patients had a history of rhabdomyolysis, and the recorded CK level ranged between 67 and 90 000 IU/l. Three patients had a history of exertional myalgia, and one patient had a non‐fluctuating weakness. Through next‐generation sequencing analysis, we identified six cases with variants in the ACADVL gene and a confirmed diagnosis of VLCADD. Of the total six variants identified, five were missense, and one was a novel frameshift mutation identified in two unrelated individuals. Two variants were novel, and three were previously reported. We treated the patients with a combination of L‐carnitine, Coenzyme Q10 and riboflavin. Three patients responded favorably to the treatment. Conclusion: Adult‐onset VLCADD is a rare entity with various presentations. Patients may respond favorably to a cocktail of L‐carnitine, Coenzyme Q10, and riboflavin.